Spatial frequency processing in the central and peripheral visual field during scene viewing. (October 2016) - Cajar, Anke; Engbert, Ralf; Laubrock, Jochen
Highlights: Low-pass filter cutoff affects fixation duration (FD), high-pass cutoff does not. The size of central low-pass or high-pass filters does not affect FD. FD is more sensitive to filter characteristics in peripheral than central vision. Filter cutoff and size often affect either FD or saccade amplitude but not both. Abstract: Visuospatial attention and gaze control depend on the interaction of foveal and peripheral processing. The foveal and peripheral regions of the visual field are differentially sensitive to parts of the spatial-frequency spectrum. In two experiments, we investigated how the selective attenuation of spatial frequencies in the central or the peripheral visual field affects eye-movement behavior during real-world scene viewing. Gaze-contingent low-pass or high-pass filters with varying filter levels (i.e., cutoff frequencies; Experiment 1) or filter sizes (Experiment 2) were applied. Compared to unfiltered control conditions, mean fixation durations increased most with central high-pass and peripheral low-pass filtering. Increasing filter size prolonged fixation durations with peripheral filtering, but not with central filtering. Increasing filter level prolonged fixation durations with low-pass filtering, but not with high-pass filtering. These effects indicate that fixation durations are not always longer under conditions of increased processing difficulty. Saccade amplitudes largely adapted to processing difficulty: amplitudes increased with central filtering and decreased with peripheral filtering; the effects strengthened with increasing filter size and filter level. In addition, we observed a trade-off between saccade timing and saccadic selection, since saccade amplitudes were modulated when fixation durations were unaffected by the experimental manipulations. We conclude that interactions of perception and gaze control are highly sensitive to experimental manipulations of input images as long as the residual information can still be accessed for gaze control.